Ratings of Affective and Non-Affective Aspects of German Idioms in Second Language Processing - Petrič, Teodor (Theory and Practice of Second Language Acquisition, 2019)
Abstract In this paper psycholinguistic and emotional properties of 619 German idiomatic expressions are explored. The list of idiomatic expressions has been adapted from Citron et al. (2015), who have used it with German native speakers. In our study the same idioms were evaluated by Slovene learners of German as a foreign language. Our participants rated each idiom for emotional valence, emotional arousal, familiarity, concreteness, ambiguity (literality), semantic transparency and figurativeness. They also had the task to describe the meaning of the German idioms and to rate their confidence about the attributed meaning. The aims of our study were (1) to provide descriptive norms for psycholinguistic and affective properties of a large set of idioms in German as a second language, (2) to explore the relationships between psycholinguistic and affective properties of idioms in German as a second language, and (3) to compare the ratings of the German native speakers studied in Citron et al. (2015) with the ratings of the Slovene second language learners from our study. On one hand, the results of the Slovene participants show many similarities with those of of the German native speakers, on the other hand, they show a slight positivity bias and slightly shallower emotional processing of the German idioms. Our study provides data that could be useful for future studies investigating the role of affect in figurative language in a second language setting (methodology, translation science, language technology).